Value co-creation process and measurement in 4.0 SMEs: An exploratory research in a B2B marketing innovation context - Marcelo Royo-Vela; Mariell Velasquez Serrano (Administrative Sciences, 2021)
The purpose of this exploratory research is to contribute to the lack of empirical research exploring techniques and protocols that can be used to measure the level of value obtained from using these technologies in the various marketing processes and in a business-to-business (B2B) context. By doing so, firms operating in fast changing dynamic environments can develop the right means to continuously adapt, integrate, reconfigure, and redeploy resources and capabilities to become more competitive and disruptive in their offerings. The phenomenon of interest is described by applying a case study qualitative approach to three 4.0 companies which use virtual reality (VR)/augmented reality (AR) technologies and by carrying out ten in-depth interviews to managers in those organizations. Results show that some small and medium sized enterprises (SMEs) are more rigorous about performance and tracking metrics compared to other companies providing similar technological services. In this line, results show two stages where potential value can be generated and measured when utilizing VR/AR technologies. The first is during testing and development of VR/AR simulations. In this stage, only the ones with strong research and academic background have been developing and using tracking systems, guidelines, and protocols as resources to measure the value obtained from using these technologies in marketing innovation processes. The second moment where value creation can be measured is during the implementation of the VR/AR simulation with the target user. Further research is needed to develop standardization guidelines and protocols that guarantee the success of the simulations delivered to the hiring firms.
Keywords: 350; 4.0 industry; B2B; case study; marketing innovation; value co-creation